Germany, 1890–1945 democracy and dictatorship : period study - Banham, Dale (Engaging with AQA GCSE (9-1) history, 2019)
Exam board: AQA Level: GCSE Subject: History First teaching: September 2016 First exams: Summer 2018 Make AQA GCSE History more accessible, enjoyable and manageable, equipping students with the depth of knowledge and complex thinking skills required for exam success. Based on his experience of teaching the specification for two years, renowned author Dale Banham uses the latest thinking on memory and visible learning to raise attainment for students of all abilities. - Engage students with accessible routes into challenging topics: the text is broken down into bullet points and boxes, while stories about interesting people start each chapter, providing a memorable 'hook' for revision - Encourage students to take responsibility for their learning: tasks are structured around five 'steps to success', teaching students how to Research, Summarise, Connect, Apply and Review the content - Make learning stick: techniques such as interleaving, retrieval practice, dual coding and spaced practice help students to remember everything and use their knowledge effectively in the exams - Build top-grade skills: the higher-order thinking skills required to construct complex arguments and reach the upper levels of the AQA mark schemes are carefully modelled, with step-by-step advice - Improve exam results: practice questions, revision tips and guidance based on the examiners' reports are embedded throughout the book, alongside purposeful homework activities for each week - Cover the content in one term: a double-page spread for each lesson and a clear pathway through each unit focuses students on what they really need to know, leaving one final term for revision.